Promosi, Harga, dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen - Andaru Setiawan Avicenna; Retno Endah Supeni; Achmad Hasan Hafidzi (BUDGETING : Journal of Business, Management and Accounting, 2022)
The purpose of this study was to determine the effect of promotion, price and service quality on the purchasing decisions of Grabfood consumers in the city of Jember during the Covid-19 pandemic. This research method is quantitative and includes explanatory research. The sample of this study used the Ferdinand formula with purposive sampling technique. Data analysis used multiple linear regression. The results of this study indicate, the results of the T test are, a) the promotion variable has a significant value of 0.000 and less than 0.05; b) the price variable has a significant value of 0.142 and is greater than 0.05; c) the service quality variable has a significance value of 0.000 and less than 0.05. In conclusion, there is a significant influence between promotion, price and service quality on decisions to use Grabfood services in Jember City during the Covid-19 pandemic. Keywords: Price, Purchase Decision, Service Quality, Promotion